Electricity restructuring in Britain not a model to follow. - MacGregor, T.
The model on which US electric industry deregulation was based is, after 10 years, a failure. The system, established in Britain in 1989, was designed and created through a nondemocratic process-without public participation or transparent information about the cost data underlying prices. Although world oil and natural gas prices plummeted, and electricity employment was reduced by 50 percent, generating prices in the UK remained so far above the cost of production that the power companies literally did not know what to do with all their profits. Unfortunately, Britain's market-based electricity pricing system became the model for restructuring around the world, including the United States. The model has spread despite its failure to do what it was supposed to do: namely, reduce prices for consumers. Even as the United States has moved to deregulate wholesale electricity prices and taken steps in some states toward market pricing of retail sales, one major difference between the restructured electric systems in Britain and the United States remains: in the United States, stakeholders participate fully in the process. Another difference is that, instead of being allowed to claim that cost data are confidential and not to be shared, US electric companies must provide information to the regulators and to the public that will allow ?just and reasonable? rates to be determined. The hope for restoration of reasonable pricing lies in the fact that the people affected by the outcomes are participating in the decisions being made: through litigation, negotiation, and legislation
Keywords: Britain; US electric companies; US electric industry deregulation; Cost data; Electricity restructuring; Generating prices; Market pricing; Market-based electricity pricing system; Production cost; Retail sales; Wholesale electricity prices deregulation